PRODUKTIFITAS LEBAH Trigona sp. PADA BERBAGAI TEKNIK BUDIDAYA DI DESA NAYAGATI KECAMATAN LEUWIDAMAR KABUPATEN LEBAK - Setiawan, Anang; Susdiyanti, Tun; Meiganati, Kustin Bintani (Jurnal Nusa Sylva, 2021)
Non-Timber Forest Products (HHBK) have been used by communities around the forest. Apart from being easy to obtain and not requiring complicated technology to get it, it also has high economic value. It is believed that the existence of NTFPs is most closely related to the interests of the community, especially the people living around the forest, in fulfilling their daily needs. One of the NTFPs products is honey bee which has high economic and utility value. This study aims to determine the bee cultivation technique of Trigona sp. which produces the highest hive weight and bee product. This research is located in Bulakan Village, Nayagati Village, Leuwidamar District, Lebak Regency. The research was conducted for 3 (three) months from August to December 2019. The research method was by observing the weight of the hive and yield of bee products, and analyzed descriptively. The results showed that the bee cultivation technique that produced the highest productivity in terms of hive weight yield, honey, propolis and brood bee was the cage technique, and the factors that caused differences in productivity were the source of feed and the presence of predators. In the cultivation of bees Trigona sp. The source of feed is very important, besides the need for monitoring every day to avoid predators.